An approach to allograft renal biopsy interpretation for the beginner- A narrative review - Swarnalata Gowrishankar (Indian Journal of Transplantation, 2020)
Allograft renal biopsy remains the gold standard for diagnosing many conditions in the transplant recipient including rejections, infections, recurrent, and de-novo renal disease. The Banff schema of reporting is followed worldwide in arriving at the right diagnosis. The guidelines, the categories, and the Banff scores in this schema are constantly evolving and this has made the interpretation of the biopsy seem complex and difficult especially for the novice. In this review, a detailed description of the various patterns of injury specific to the graft, the Banff categories of diagnoses, the lesions, and the Banff scores are simplified and explained. Lastly, a systematic approach to these allograft biopsies, which can be followed in regular practice, and by which a tentative diagnosis can be made in most cases is laid out.